Effect of perioperative individualized nutrition intervention on pancreatic surgery outcomes: a prospective single-center study - Qing Chen; Chunhong Xiao; Xusangni Li; Qian Li; Huishuang Wu; Meiping Wang; Weixuan Hong; Aiwen Huang (Journal of Health, Population and Nutrition)
Abstract Background There is currently a lack of reports on prospective randomized controlled trials (RCTs) focused on personalized nutritional support in pancreatic surgery. This study aimed to evaluate the impact of perioperative individualized nutritional intervention on the outcomes of patients undergoing pancreatic surgery within the framework of enhanced recovery after surgery (ERAS). Methods This prospective cohort study enrolled 96 patients, randomly divided into a trial group and a control group in a 1:1 ratio. The primary endpoint was the change in body composition, including body cell mass (BCM), fat-free mass (FFM), skeletal muscle mass (SMM), and phase angle (PA). Secondary outcomes included time to first postoperative flatus, time to first bowel movement, length of hospital stay, and nutritional indicators. Results No significant differences were observed in the demographic characteristics between the two groups. The ratio of actual total calorie intake to recommended daily intake in the trial group was significantly higher than the control group (87.01% vs. 69.50%, P < 0.001). The ratio of actual protein intake to recommended daily intake was significantly higher in the trial group than the control group (96.18% vs.76.29%, P < 0.001). In body composition data, significant differences were found between the two groups in the ratio of BCM, FFM, and SMM at the study endpoint compared to admission. Additionally, a significant difference between the two groups was present in the ratio of BCM, FFM, and SMM at the third postoperative day (POD 3) compared with those at admission. While no significant differences were found between the groups in time to first flatus and time to first stool, the trial group had a significantly shorter postoperative hospital stay compared to the control group (15.9d vs. 20.4d, P = 0.046). Nutritional index analysis revealed a statistically significant difference in the ratio of serum total protein at the study endpoint compared POD 3 (P < 0.05), but no significant differences were found in serum prealbumin, albumin, and hemoglobin. Conclusions Personalized nutritional interventions throughout the perioperative period improved patients’ nutritional status and reduced the length of postoperative hospital stay.